2011
DOI: 10.4049/jimmunol.1003238
|View full text |Cite
|
Sign up to set email alerts
|

A TLR5 Agonist Inhibits Acute Renal Ischemic Failure

Abstract: Reperfusion of ischemic organs induces a potent inflammatory response initiated by the generation of reactive oxygen species (ROS) that directly damage tissue and promote leukocyte infiltration and activation that also mediate tissue injury. We recently found that radiation-induced tissue injury, which is caused by radiation induced ROS, is attenuated by administration of CBLB502, a pharmacologically optimized derivative of the Toll-like receptor 5 (TLR5) agonist flagellin. Therefore, we tested the ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 50 publications
0
31
1
Order By: Relevance
“…Because of its lower toxicity and lower immunogenicity, CBLB502 emerges as a more attractive TLR5 agonist and is currently undergoing phase I clinical trial. Mean-while, preclinical studies with mouse models have shown that CBLB502 can inhibit acute renal ischemic failure and can protect mice from dermatitis caused by local cancer radiotherapy (30,31). These reports support a notion that CBLB502 may be an effective agent in modulating beneficial immune responses.…”
mentioning
confidence: 61%
“…Because of its lower toxicity and lower immunogenicity, CBLB502 emerges as a more attractive TLR5 agonist and is currently undergoing phase I clinical trial. Mean-while, preclinical studies with mouse models have shown that CBLB502 can inhibit acute renal ischemic failure and can protect mice from dermatitis caused by local cancer radiotherapy (30,31). These reports support a notion that CBLB502 may be an effective agent in modulating beneficial immune responses.…”
mentioning
confidence: 61%
“…Such factors may play roles in CBLB502's protection of (i) the HP and GI systems against radiation (8), (ii) the kidney against ischemia-reperfusion injury (10), and (iii) the liver against Fas-mediated apoptosis (this report). In these cases, additional "prosurvival" TLR5 agonist responses may include those controlled by the STAT3 (47,48) and AP-1 pathways (49), which were previously shown to be responsible for liver resistance to Fas-mediated apoptosis (35), as well as by the PBREM, which regulates genes involved in the detoxifying metabolic capacity of the liver (50).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, CBLB502 protected mice from dermatitis and mucositis associated with local fraction irradiation of head and neck area modeling radiation treatment of patients with head and neck cancer (9). Second, the TLR5 agonist CBLB502 was shown to be effective as a tissue protectant in mouse models of renal ischemia-reperfusion injury (10). Third, bacterial flagellin and flagellin-expressing bacteria (Salmonella) have shown antitumor effects in mouse models of colon and liver metastasis of pancreatic cancer (11,12).…”
mentioning
confidence: 99%
“…CBLB502 exerts radioprotective activities and inhibits acute renal ischemic failure (8)(9)(10)12). In this study, we examined the treatment of UC using CBLB502 via the effects of CBLB502 on TLR responses and IL and NF-κB signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…CBLB502 exerts radioprotective activity and is characterized as safe and highly effective in reducing the risk of death by activating nuclear factor kappa B (NF-κB) pathway (8). CBLB502 inhibits acute renal ischemic failure and is protective when given 30 min before and after ischemic kidney reperfusion (9). CBLB502 can significantly reduce the severity of dermatitis and oral mucositis caused by local radiation, and these properties are mediated via the activation of TLR5 signaling (10).…”
Section: Introductionmentioning
confidence: 99%